Attempts to separate (–)‐α‐thujone, (+)‐β‐thujone epimers from camphor enantiomers by enantioselective HPLC with polarimetric detection. Issue 5 (4th February 2013) - El Montassir, Dahmane; Aamouche, Ahmed; Vanthuyne, Nicolas; Jean, Marion; Vanloot, Pierre; Taourirte, Moha; Dupuy, Nathalie; Roussel, Christian
<x xml:space="preserve">Abstract</x> In a first step, 26 chiral stationary phases (CSPs) have been screened for the separation of (–)‐α‐thujone, (+)‐β‐thujone epimers and camphor enantiomers by LC. The separations were monitored by a polarimeter detector. None of these CSPs provided a noticeable resolution for camphor enantiomers. The three components of a test mixture were clearly baseline separated on Chiralpak AS‐H, Chiralpak AZ‐H and TCI‐MBS (poly(N‐alpha‐(S)‐methylbenzylmaleimide) coated on silica gel) in a mobile phase composed of hexane/2‐PrOH (99:1 v/v). Interestingly, for a preparative application, the three CSPs produced different elution orders for the three constituents of the mixture. In a second step, it is shown that the use of online polarimetric detection constitutes an unprecedented method to reveal the occurrence and the relative content of thujone epimers and the chirality of the major camphor enantiomer in crude essential oils. A proof of concept is illustrated on crude essential oils from Rosmarinus tournefortii, Artemisia herba alba and A. arborescens, which grow in Morocco and have several traditional uses there. In a third step, pure (+)‐β‐thujone was quantitatively collected from A. arborescens crude oil by semi‐preparative HPLC on Chiralpak AZ‐H monitored by a polarimeter.